2022
DOI: 10.12776/qip.v26i3.1766
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Social and Governance Information Disclosure Strategy of the Ten Main Spanish Listed Companies

Abstract: Purpose: This article aims to investigate the environmental, social, and corporate governance (ESG) disclosure strategy and its impact on the financial performance of the top ten companies in terms of operating income/turnover volume. Methodology/Approach: The study methods used include parametric correlations and logistic regression analysis focusing on data from Spanish listed companies in 2019-2020. Findings: The findings show that IBEX35 companies need to improve web transparency in ESG reporting and a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…We also find differences between the levels of ESG information analyzed using the TBL philosophy. These results confirm Spain as an interesting case study because Spanish companies in general obtain high scores in various sustainability indices (García‐Sánchez, 2021; Gutierrez‐Ponce et al, 2022; Gutiérrez‐Ponce, Chamizo‐González, & Arimany‐Serrat, 2022; KPMG, 2020; Sierra‐Garcia et al, 2018; Tarquinio et al, 2018). Spain was also a pioneer in making external verification of sustainability reports mandatory.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…We also find differences between the levels of ESG information analyzed using the TBL philosophy. These results confirm Spain as an interesting case study because Spanish companies in general obtain high scores in various sustainability indices (García‐Sánchez, 2021; Gutierrez‐Ponce et al, 2022; Gutiérrez‐Ponce, Chamizo‐González, & Arimany‐Serrat, 2022; KPMG, 2020; Sierra‐Garcia et al, 2018; Tarquinio et al, 2018). Spain was also a pioneer in making external verification of sustainability reports mandatory.…”
Section: Resultssupporting
confidence: 55%
“…Corporate sustainability reports must be analyzed to identify and define companies' economic and sustainability models, as well as their commitment to the SDGs. Although multiple studies (García‐Sánchez, 2021; Gutierrez‐Ponce et al, 2022; Gutiérrez‐Ponce, Chamizo‐González, & Arimany‐Serrat, 2022; Sierra‐Garcia et al, 2018; Tarquinio et al, 2018) indicate that Spanish companies obtain high scores on their sustainability reports, few studies analyze the relationship between sustainability reports (ESG) and the SDGs in the Spanish context. This paper aims to fill this research gap for Spanish listed companies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also showed a significant relationship between financial indicators and ESG transparency. (Gutierrez-Ponce et al, 2022). A comprehensive study was conducted on combined reports by examining the factors influencing the level of information disclosures of sustainability (SR) and integrated reports (IR) in Kenya.…”
Section: Integrated Reporting/ Sustainability Reporting/esg Reportingmentioning
confidence: 99%
“…Controversies and scandals regarding the role of banks in the crisis have also revealed failures in some dimensions of sustainability—environmental, social, and governance (ESG)—raising questions about banks' social responsibility policies, such as their real strategic commitment to main stakeholders (Esteban‐Sanchez et al, 2017; Hoang, 2023). The relationship between the performance of ESG activities and FP has been studied in companies from different sectors and regions, with studies obtaining a significant relationship between financial indicators and ESG information (Galletta et al, 2022; Gutierrez‐Ponce et al, 2022). More specifically, (Buallay et al, 2023) study the sustainability report in the banking sector in different economic and political environments and find a negative relationship between the ESG pillars and FP.…”
Section: Introductionmentioning
confidence: 99%